The Causal Nexus between Exports and Economic Growth: Evidence on the Role of Omitted Variables - Keho, Yaya (International Journal of Economics and Financial Issues, 2018)
Over the past two decades, the export-growth nexus has been extensively investigated yielding to inconclusive findings. Most of existing studies used a bivariate framework ignoring the role of other relevant variables. This study re-examines the nexus for 12 African countries by incorporating capital, labor, and imports into the analysis. The results are sensitive to the inclusion of controlling variables. Within the bivariate framework, we found long-run relationships between export and output in eight countries and the export-led growth hypothesis holds in Benin, Burkina Faso, Cameroon, Gabon, Ghana, Nigeria, and South Africa. However, when capital, labor and imports are controlled for, the results show long-run relationships among the variables in all countries and the export-led growth hypothesis holds in Cameroon, Cote d'Ivoire, Gabon, Ghana, Senegal, and South Africa. These results highlight the risk of misleading conclusions based on bivariate models. Keywords: Export, import, economic growth JEL Classifications: F14, F43, O4